Prediction of flow characteristics in the bubble column reactor by the artificial pheromone-based communication of biological ants - Shamshirband, Shahaboddin; Babanezhad, Meisam; Mosavi, Amir; Nabipour, Narjes; Hajnal, Eva; Nadai, Laszlo; Chau, Kwok-Wing (Engineering applications of computational fluid mechanics, 2020)
A novel combination of the ant colony optimization algorithm (ACO)and computational fluid dynamics (CFD) data is proposed for modeling the multiphase chemical reactors. The proposed intelligent model presents a probabilistic computational strategy for predicting various levels of three-dimensional bubble column reactor (BCR) flow. The results prove an enhanced communication between ant colony prediction and CFD data in different sections of the BCR.